Effect of calcination temperature on dielectic properties of CaCu3Ti4O12 ceramics - M. F. A. Rahman; Z. A. Ahmad; M. F. Ain; J. J. Mohamed (2016)
The effect of calcination temperature on the properties of CaCu3Ti4O12 (CCTO) ceramics was studied. CCTO ceramics were prepared using solid state reaction method. The raw materials of CCTO were wet mixed for 24 hours and was dried overnight. CCTO powders were then calcined at three different temperature which is at 900̊C, 930̊C and 985̊C for 12 hours. The calcined powders were compacted at 250 MPa and then were sintered at 1040̊C for 10 hours. X-Ray Diffractometer (XRD) analysis showed the formation of CCTO phase and secondary phases of CuO for C900 calcined powder but single phase of CCTO was obtained by C930 and C985 calcined powders. Single phase of CCTO also were seen for all sintered samples. Observation on Scanning Electron Microscopy (SEM) micrographs showed abnormal grain growth or large grain size was seen in C900 sample and finer grain size was observed for C930 and C985 sintered samples. C900 sintered sample obtained the highest dielectric constant (10,462) and the lowest dielectric loss (0.061) measured at 1 MHz.